Off-shell energy effects in multiple scattering of protons on deuterons at the energy of 1 GeV - V. V. Davydovskyy (Ядерна фізика та енергетика)
Investigation of high energy proton scattering of the deuterium nuclei is carried out in the framework of the new approach using three-dimensional generalized profile function of the nucleon, which allows taking into account the offshell energy effects in the intermediate acts of scattering. Cross sections of the elastic scattering of protons with the energy of 1 GeV on the deuterons are calculated. The obtained results of the calculation are compared with the experimental data as well as with the calculations within the common Glauber - Sitenko diffraction theory.